Current collector, secondary battery, battery module, battery pack, and electric device
Patent Information
- Application Number
- CN202280096276.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-21
- Publication Date
- 2024-12-27
AI Technical Summary
During the charging and discharging process of existing secondary batteries, side reactions between metals and electrolytes seriously affect the stability of the interface, resulting in a decrease in the electrochemical performance and safety performance of the battery, and cannot meet the application needs of the new generation of electrochemical systems.
Using a coated current collector, the coating includes an interface protective layer and an induced deposition layer. The interface protective layer is located on one side of the current collector, and the induced deposition layer is located on the other side of the current collector. By reducing the contact between the metal and the electrolyte, the The nucleation overpotential of metal ions regulates deposition behavior, inhibits dendrites, and reduces side reactions.
It effectively improves the Coulombic efficiency and cycle capacity retention rate of the battery, extends the service life of the battery, and enhances the stability and safety of the battery.
Smart Images

Figure CN119213595A_ABST
Abstract
Description
Current collector, secondary battery, battery module, battery pack and power-consuming device Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a current collector, a secondary battery, a battery module, a battery pack, and an electrical device. Background Art
[0002] In recent years, secondary batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields.
[0003] Interface stability is an important indicator for measuring secondary batteries. Side reactions between metals and electrolytes will seriously affect the stability of the interface, resulting in a decline in the electrochemical performance and safety performance of the battery, which cannot meet the application needs of the new generation of electrochemical systems.
[0004] Summary of the Invention
[0005] The present application is made in view of the above-mentioned problems, and its purpose is to provide a current collector with a coating, which is beneficial to reduce the contact between the metal deposited on the current collector and the electrolyte, thereby reducing the side reactions between the metal and the electrolyte and improving the coulombic efficiency and cycle performance of the battery.
[0006] In a first aspect of the present application, a current collector having a coating is provided, wherein the coating comprises at least an interface protection layer, and the coating is formed on at least one side of the current collector.
[0007] During charge and discharge, metal ions can freely pass through the interfacial protective layer. Metal deposited on the current collector or deintercalated from the current collector can pass through the interfacial protective layer in the form of metal ions. In other words, during charge and discharge, the interfacial protective layer is located between the metal phase and the electrolyte, which helps reduce contact between the metal and the electrolyte, thereby reducing the occurrence of side reactions between the metal and the electrolyte, effectively improving the battery's coulombic efficiency and cycle capacity retention.
[0008] In any embodiment, the coating further includes an induced deposition layer, and the induced deposition layer and the interface protection layer are sequentially arranged in a direction from close to the current collector to away from the current collector.
[0009] An induced deposition layer and an interface protection layer are sequentially disposed on one side of the current collector. This reduces the nucleation overpotential of metal ions, induces uniform deposition of metal ions, regulates metal ion deposition behavior, inhibits dendrite formation, and reduces contact between the metal and the electrolyte, thereby reducing the occurrence of side reactions between the metal and the electrolyte, effectively improving the battery's coulombic efficiency and cycle capacity retention. In any embodiment, the induced deposition layer is in direct contact with the surface of the current collector.
[0010] In any embodiment, the induced deposition layer is in direct contact with the surface of the current collector.
[0011] In any embodiment, the interface protection layer is in direct contact with the surface of the induced deposition layer.
[0012] The formation of an induced deposition layer on the surface of the current collector and an interface protection layer on the surface of the induced deposition layer can reduce the nucleation overpotential of metal ions and reduce the contact between metal and electrolyte, thereby effectively improving the performance of the battery.
[0013] In any embodiment, the interface protection layer comprises one or more of polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene copolymer, polyacrylic acid, and polyimide, and optionally comprises one or more of polyvinylidene fluoride and carboxymethyl cellulose.
[0014] The interface protective layer comprises one or more of polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene copolymer, polyacrylic acid, and polyimide, which is beneficial for improving the coulombic efficiency and cycle capacity retention of the battery. The interface protective layer comprises one or more of polyvinylidene fluoride and carboxymethyl cellulose, which can significantly reduce the nucleation overpotential of metal ions, further improving the coulombic efficiency and cycle capacity retention of the battery.
[0015] In any embodiment, the thickness of the interface protection layer is 15 nm to 1500 nm, and can be optionally 50 nm to 500 nm.
[0016] Controlling the thickness of the interface protection layer to 15nm to 1500nm is beneficial to improving the battery's coulombic efficiency and cycle capacity retention rate or reducing the nucleation overpotential of metal ions, providing effective protection while avoiding excessive thickness that leads to an increase in battery internal resistance and a decrease in battery cycle performance and energy density. Controlling the thickness of the interface protection layer to 50nm to 500nm is beneficial to further improving the battery's coulombic efficiency and cycle capacity retention rate or to further reduce the nucleation overpotential of metal ions.
[0017] In any embodiment, the induced deposition layer comprises a conductive material, and the conductive material comprises a carbon material and / or a metal material.
[0018] The induced deposition layer containing conductive materials is beneficial to reducing the nucleation overpotential of metal ions and improving the coulombic efficiency and cycle capacity retention rate of the battery.
[0019] In any embodiment, the conductive material comprises one or more of Super P, carbon nanotubes, hard carbon, two-dimensional graphene, graphene quantum dots, gold, silver, copper, aluminum, iron, and nickel, and optionally comprises one or more of Super P, carbon nanotubes, hard carbon, two-dimensional graphene, and graphene quantum dots.
[0020] The induced deposition layer containing the above materials is beneficial for reducing the nucleation overpotential of metal ions and improving the coulombic efficiency and cycle capacity retention of the battery. Compared with the induced deposition layer containing metal materials, the induced deposition layer containing carbon materials has a lower metal ion nucleation overpotential and a higher battery coulombic efficiency and cycle capacity retention.
[0021] In any embodiment, the thickness of the induced deposition layer is 50 nm to 2000 nm, and can be optionally 200 nm to 1000 nm.
[0022] Controlling the thickness of the induced deposition layer to 50nm to 2000nm can provide sufficient nucleation sites, which is beneficial to reducing the nucleation overpotential of metal ions and improving the coulombic efficiency and cycle capacity retention of the battery. At the same time, it avoids excessive thickness leading to increased side reactions and a decrease in battery energy density. Controlling the thickness of the induced deposition layer to 200nm to 1000nm is beneficial to further reduce the nucleation overpotential of metal ions and further improve the coulombic efficiency and cycle capacity retention of the battery.
[0023] In any embodiment, the induced deposition layer further comprises a binder, and the binder comprises one or more selected from polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene copolymer, polyacrylic acid, and sodium alginate.
[0024] The binder provides high adhesion between the induced deposition layer and the current collector, thereby preventing desorption of the current collector and also facilitating uniform distribution of the conductive carbon material in the induced deposition layer.
[0025] In any embodiment, the binder material in the induced deposition layer is at least partially the same as the material of the interface protection layer.
[0026] Controlling the binder material in the induced deposition layer to be at least partially identical to the material of the interface protection layer increases the compatibility between the interface protection layer and the induced deposition layer, which is beneficial to reducing the nucleation overpotential of metal ions and improving the coulombic efficiency and cycle capacity retention rate of the battery.
[0027] In any embodiment, the current collector includes at least one of a metal foil, a metal foam current collector, a metal mesh current collector, a carbon felt current collector, a carbon cloth current collector, a carbon paper current collector, and a composite current collector.
[0028] The above-mentioned current collector has excellent tensile strength and ductility, which is beneficial to the stability and safety of the battery.
[0029] A second aspect of the present application provides a secondary battery comprising an electrolyte and a negative electrode plate, wherein the negative electrode plate comprises a current collector in any embodiment.
[0030] The secondary battery has excellent cycle performance.
[0031] In any embodiment, the secondary battery includes at least one of a lithium battery and a sodium battery.
[0032] In any embodiment, the secondary battery is a negative electrode-free sodium battery. The negative electrode-free sodium battery can have a high energy density.
[0033] In any embodiment, the electrolyte contains an ether solvent, and the ether solvent contains one or more of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, 1,3-dioxolane, tetrahydrofuran, methyltetrahydrofuran, diphenyl ether, and crown ether, and optionally contains one or more of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, and diethylene glycol dimethyl ether.
[0034] Electrolytes containing the aforementioned solvents are all beneficial in reducing the overpotential of sodium ions and improving the coulombic efficiency and cycle capacity retention of the battery. Solvents containing one or more of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, and diethylene glycol dimethyl ether are beneficial in further improving the coulombic efficiency and cycle capacity retention of the battery.
[0035] In any embodiment, the electrolyte further includes a sodium borate additive.
[0036] Sodium borate additives react with metals to form boron-rich inorganic compounds, which in turn form an organic / inorganic composite protective layer with the interfacial protective layer, improving the battery's cycling performance. Furthermore, if the SEI membrane is damaged during battery cycling, sodium borate additives can continuously generate boron-rich inorganic compounds to repair the damage, further enhancing the battery's cycling performance.
[0037] In any embodiment, the sodium borate additive includes one or more of sodium difluorooxalatoborate, sodium tetrafluoroborate, sodium bisoxalatoborate, and sodium tetraphenylborate, and optionally includes one or more of sodium difluorooxalatoborate and sodium bisoxalatoborate.
[0038] The electrolyte containing the above sodium borate additive is beneficial to improving the coulombic efficiency and cycle capacity retention rate of the battery.
[0039] In any embodiment, based on the total mass of the electrolyte, the mass content of the sodium borate additive is 0.01% to 1.8%, and can be optionally 0.1% to 1.0%.
[0040] Controlling the mass content of sodium borate additives to 0.01% to 1.8% is beneficial to improving the coulombic efficiency and cycle capacity retention rate of the battery. Controlling the mass content of sodium borate additives to 0.1% to 1.0% can further improve the coulombic efficiency and cycle capacity retention rate of the battery.
[0041] A third aspect of the present application provides a battery module, comprising the secondary battery according to the second aspect of the present application.
[0042] A fourth aspect of the present application provides a battery pack, comprising the secondary battery of the second aspect of the present application or the battery module of the third aspect of the present application.
[0043] A fifth aspect of the present application provides an electrical device comprising at least one of the secondary battery of the second aspect of the present application, the battery module of the third aspect of the present application, and the battery pack of the fourth aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] FIG1 is a schematic diagram of a secondary battery according to an embodiment of the present application;
[0045] FIG2 is an exploded view of the secondary battery according to one embodiment of the present application shown in FIG1 ;
[0046] FIG3 is a schematic diagram of a battery module according to an embodiment of the present application;
[0047] FIG4 is a schematic diagram of a battery pack according to an embodiment of the present application;
[0048] FIG5 is an exploded view of the battery pack according to an embodiment of the present application shown in FIG4 ;
[0049] FIG6 is a schematic diagram of an electric device using a secondary battery as a power source according to an embodiment of the present application.
[0050] Description of reference numerals:
[0051] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 cover plate. DETAILED DESCRIPTION
[0052] Below, the embodiments of the current collector, secondary battery, battery module, battery pack and power device of the present application are described in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0053] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0054] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0055] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0056] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0057] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.
[0058] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0059] Metal secondary batteries are secondary batteries that use metal materials (such as lithium, sodium, magnesium, potassium, and other metals) as their negative electrodes. The metal material on the negative electrode current collector can be pre-deposited on the current collector surface as a negative electrode active material, or it can be deposited in situ on the current collector surface during the charge and discharge process. This means that metal secondary batteries include sodium batteries, lithium batteries, magnesium batteries, potassium batteries, and other batteries with negative electrode active materials, as well as batteries without negative electrodes. The negative electrode sheet in a battery without negative electrodes uses a negative electrode current collector and does not contain negative electrode active materials. During the initial charge and discharge process, metal ions are deposited in situ on the negative electrode current collector.
[0060] There are currently many problems with metal batteries. Taking the negative electrode-free sodium battery as an example, during the charging and discharging process, side reactions are likely to occur between metallic sodium and the electrolyte, consuming a large amount of sodium elements and reducing the battery's coulombic efficiency and cycle performance.
[0061] [current collector]
[0062] Based on this, the present application proposes a current collector with a coating, wherein the coating includes at least an interface protection layer, and the coating is formed on at least one side of the current collector.
[0063] The interfacial protective layer protects the metal by reducing contact between the metal and the electrolyte, thereby reducing side reactions between the metal and the electrolyte. The interfacial protective layer is located between the current collector and the electrolyte, and allows metal ions to pass freely through the interfacial protective layer. During charging, metal ions pass from the electrolyte through the interfacial protective layer and are deposited on the current collector. During discharge, the metal loses electrons and desorbs from the current collector as metal ions, diffusing through the interfacial protective layer into the electrolyte.
[0064] As used herein, the term "at least one side of a current collector" refers to at least one side of a surface of a current collector.
[0065] In some embodiments, the interfacial protection layer is a polymer layer.
[0066] In some embodiments, the current collector serves as a negative electrode current collector of a secondary battery.
[0067] In some embodiments, the current collector serves as a negative electrode current collector of a negative electrode-free battery, and the interface protection layer is in direct contact with the surface of the current collector.
[0068] In some embodiments, the current collector is a negative electrode current collector of a metal battery, and a metal phase is present between the interface protection layer and the current collector.
[0069] The interface protection layer helps to reduce the contact between the metal and the electrolyte, thereby reducing the occurrence of side reactions between the metal and the electrolyte, effectively improving the coulombic efficiency of the battery and the capacity retention rate after 100 cycles.
[0070] In this article, coulombic efficiency refers to the first coulombic efficiency, which is mainly used to characterize the ratio of battery discharge capacity to charge capacity during the first cycle, and can reflect the degree of metal ion consumption. It can be tested by any known method.
[0071] In this article, the capacity retention rate after 100 cycles is mainly used to characterize the cycle performance of the battery and can reflect the cycle performance of the battery, which can be tested by any known method.
[0072] In some embodiments, the coating further includes an induced deposition layer, and the induced deposition layer and the interface protection layer are sequentially arranged in a direction from close to the current collector to far away from the current collector.
[0073] In this paper, the induced deposition layer provides sufficient nucleation sites to induce uniform metal deposition, which is beneficial to suppress metal dendrites.
[0074] In some embodiments, one or more coating layers are located between the induced deposition layer and the current collector.
[0075] In some embodiments, a deposition layer is provided between the induced deposition layer and the interface protection layer. The deposition layer may be a metal phase pre-deposited between the current collector and the interface protection layer. The deposition layer may also be a metal phase in which metal ions are deposited onto the current collector through the interface protection layer.
[0076] The induction deposition layer and interface protection layer are sequentially arranged on the current collector to reduce the nucleation overpotential of metal ions, induce uniform deposition of metal ions, regulate metal ion deposition behavior, inhibit dendrites, and reduce the contact between the metal and the electrolyte, thereby reducing the occurrence of side reactions between the metal and the electrolyte, effectively improving the battery's coulombic efficiency and cycle capacity retention rate. In this article, the term "nucleation overpotential" refers to the potential required for metal ions to obtain electrons at the negative electrode to form metal atoms for deposition.
[0077] In this article, the nucleation overpotential is mainly used to characterize the potential required for metal ion deposition, which can characterize the uniformity of metal ion deposition and can be tested by any known method.
[0078] In some embodiments, the induced deposition layer is in direct contact with the surface of the current collector.
[0079] In some embodiments, the interfacial protection layer is in direct contact with the surface of the induced deposition layer.
[0080] The formation of an induced deposition layer on the surface of the current collector and an interface protection layer on the surface of the induced deposition layer can reduce the nucleation overpotential of metal ions and reduce the contact between metal and electrolyte, thereby effectively improving the performance of the battery.
[0081] In some embodiments, the interface protection layer comprises one or more of polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene copolymer, polyacrylic acid, and polyimide, and optionally comprises one or more of polyvinylidene fluoride and carboxymethyl cellulose.
[0082] The interface protective layer comprises one or more of polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene copolymer, polyacrylic acid, and polyimide, which is beneficial for improving the coulombic efficiency of the battery and the capacity retention rate after 100 cycles. The interface protective layer comprises one or more of polyvinylidene fluoride and carboxymethyl cellulose, which can significantly reduce the nucleation overpotential of metal ions, further improving the coulombic efficiency of the battery and the capacity retention rate after 100 cycles.
[0083] In some embodiments, the thickness of the interface protection layer is 15 nm to 1500 nm, optionally 50 nm to 500 nm. In some embodiments, the thickness of the interface protection layer may be 15 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm, 1100 nm, 1200 nm, 1300 nm, 1400 nm, or 1500 nm.
[0084] Controlling the thickness of the interface protection layer to 15nm to 1500nm is beneficial to improving the battery's coulombic efficiency and capacity retention after 100 cycles or reducing the nucleation overpotential of metal ions, providing effective protection while avoiding excessive thickness that increases the battery's internal resistance and reduces battery cycle performance and energy density. Controlling the thickness of the interface protection layer to 50nm to 500nm is beneficial to further improving the battery's coulombic efficiency and capacity retention after 100 cycles or to further reduce the nucleation overpotential of metal ions.
[0085] In some embodiments, the induced deposition layer comprises a conductive material, and the conductive material comprises a carbon material and / or a metal material.
[0086] As used herein, the term "carbon material" refers to a material comprising carbon. As examples, the carbon material includes, but is not limited to, Super P, carbon nanotubes, hard carbon, two-dimensional graphene, or graphene quantum dots.
[0087] In some embodiments, the conductive material comprises a carbon material.
[0088] In some embodiments, the conductive material comprises a metallic material.
[0089] In some embodiments, the conductive material comprises a carbon material and a metal material.
[0090] The induced deposition layer containing conductive materials is beneficial to reducing excessive local current density through good conductivity, lowering the nucleation overpotential of metal ions, and improving the coulombic efficiency of the battery and the capacity retention rate after 100 cycles.
[0091] In some embodiments, the carbon material comprises carbon nanomaterial.
[0092] In this article, the term "carbon nanomaterial" refers to a carbon material with at least one dimension in the three-dimensional space being in the nanometer size (1nm to 100nm) or composed of them as basic units, which is roughly equivalent to the scale of 10 to 1000 atoms closely packed together.
[0093] Carbon nanomaterials can easily induce the deposition of metal ions on the surface of the primer layer through adsorption. Their nanoscale structure and arrangement improve the uniformity of the distribution of nucleation sites, which is conducive to further uniform deposition of metal ions.
[0094] In some embodiments, the conductive material comprises one or more of Super P, carbon nanotubes, hard carbon, two-dimensional graphene, graphene quantum dots, gold, silver, copper, aluminum, iron, and nickel, and can be selected from one or more of Super P, carbon nanotubes, hard carbon, two-dimensional graphene, and graphene quantum dots.
[0095] As used herein, the term "Super P" refers to carbon black particles that aggregate to form grape-shaped shapes.
[0096] As used herein, the term "carbon nanotube" refers to a seamless hollow cylinder formed by rolling up a single or multiple layers of graphene, with a diameter less than 100 nm and a length greater than 100 nm. Examples of carbon nanotubes include, but are not limited to, single-walled carbon nanotubes and / or multi-walled carbon nanotubes.
[0097] As used herein, the term "hard carbon" refers to carbon that is difficult to graphitize.
[0098] In some embodiments, two-dimensional graphene refers to graphene with a sheet structure that is nanometer-sized (less than 100 nm) in the thickness direction and exceeds 100 nm in other directions. It may include single-layer graphene and / or multi-layer graphene.
[0099] As used herein, the term "single-layer graphene" refers to a single-layer sheet structure composed of carbon atoms densely arranged in a periodic hexagonal honeycomb structure. For example, the thickness of a single-layer graphene is only 0.3 nm to 0.4 nm.
[0100] In this article, the term "multilayer graphene" refers to a stack of 2 to 10 single-layer graphene layers with a total thickness of less than 100 nm.
[0101] As used herein, the term "graphene quantum dots" refers to graphene nanoparticles with graphene sizes within 100 nm in all dimensions.
[0102] The induced deposition layer containing the above materials is beneficial for reducing the nucleation overpotential of metal ions and improving the coulombic efficiency and cycle capacity retention of the battery. Compared with the induced deposition layer containing metal materials, the induced deposition layer containing carbon materials has a lower guardian ion nucleation overpotential and a higher battery coulombic efficiency and cycle capacity retention.
[0103] In some embodiments, the thickness of the induced deposition layer is 50 nm to 2000 nm, optionally 200 nm to 1000 nm. In some embodiments, the thickness of the induced deposition layer may be 50 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm, 1100 nm, 1200 nm, 1300 nm, 1400 nm, 1500 nm, 1600 nm, 1700 nm, 1800 nm, 1900 nm, or 2000 nm.
[0104] Controlling the thickness of the induced deposition layer to 50nm to 2000nm can provide sufficient nucleation sites, which is beneficial to reducing the nucleation overpotential of metal ions, improving the coulombic efficiency and cycle capacity retention of the battery, while avoiding excessive thickness leading to increased side reactions and a decrease in battery energy density. Controlling the thickness of the induced deposition layer to 200nm to 1000nm is beneficial to further reduce the nucleation overpotential of metal ions, further improving the coulombic efficiency of the battery and the capacity retention rate after 100 cycles.
[0105] As used herein, the term "nucleation site" refers to a location where metal ions are deposited by obtaining electrons at the negative electrode to form metal atoms.
[0106] In some embodiments, the induced deposition layer further comprises a binder, and the binder comprises one or more selected from polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene copolymer, polyacrylic acid, and sodium alginate.
[0107] The binder provides high adhesion between the induced deposition layer and the current collector, thereby preventing desorption of the current collector and also facilitating uniform distribution of the conductive carbon material in the induced deposition layer.
[0108] In some embodiments, the binder material in the induced deposition layer is at least partially the same as the material of the interface protection layer.
[0109] In some embodiments, the binder material in the induced deposition layer is identical to the material of the interface protection layer. For example, the binder only comprises carboxymethyl cellulose, and the interface protection layer only comprises carboxymethyl cellulose.
[0110] In some embodiments, the binder material in the induced deposition layer is partially the same as the material of the interface protection layer. For example, the binder comprises a mixture of carboxymethyl cellulose and styrene-butadiene copolymer, and the interface protection layer comprises only carboxymethyl cellulose.
[0111] Controlling the binder material in the induced deposition layer to be at least partially identical to the material of the interface protective layer increases the compatibility between the interface protective layer and the induced deposition layer, which is beneficial to reducing the nucleation overpotential of metal ions and improving the coulombic efficiency of the battery and the capacity retention rate after 100 cycles.
[0112] In some embodiments, the current collector includes at least one of a metal foil, a metal foam current collector, a metal mesh current collector, a carbon felt current collector, a carbon cloth current collector, a carbon paper current collector, and a composite current collector.
[0113] In some embodiments, the metal foil material may be copper foil, aluminum foil, stainless steel foil, iron foil, zinc foil, titanium foil, and the metal foam current collector may be copper foam, aluminum foam, zinc foam, etc. The metal mesh current collector may be copper mesh or aluminum mesh. The composite current collector includes a polymer base film and metal foil materials formed on both sides of the polymer base film. The composite current collector may be a "sandwich" structure, with the polymer base film located in the middle and metal foil materials provided on both sides. The polymer base film may be one of polyamide, polyterephthalate, polyimide, polyethylene, polypropylene, polystyrene, polyvinyl chloride, acrylonitrile-butadiene-styrene copolymer, polybutylene terephthalate, poly(p-phenylene terephthalamide), polypropylene, polyoxymethylene, epoxy resin, phenolic resin, polytetrafluoroethylene, polyvinylidene fluoride, silicone rubber, and polycarbonate.
[0114] The above-mentioned current collector has excellent tensile strength and ductility, which is beneficial to the stability and safety of the battery.
[0115] [Positive electrode]
[0116] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer formed on at least a portion of the surface of the positive electrode current collector. The positive electrode active material layer includes a positive electrode active material, which may include at least one of a layered transition metal oxide, a polyanionic compound, and a Prussian blue compound.
[0117] The transition metal in the layered transition metal oxide can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce. Optionally, the layered transition metal oxide is, for example, NaxMO2, where M is one or more of Ti, V, Mn, Co, Ni, Fe, Cr, and Cu, and 0<x≤1.
[0118] Polyanionic compounds can be metal ions, transition metal ions and tetrahedral (YO4) n- A class of compounds with anionic units. The metal ion can be selected from sodium ion, lithium ion, potassium ion, and zinc ion; the transition metal can be selected from at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce; Y can be selected from at least one of P, S, and Si; n represents (YO4) n- valence.
[0119] Prussian blue compounds can be compounds containing sodium ions, transition metal ions, and cyanide ions (CN-). The transition metal can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce. Prussian blue compounds are, for example, Na a Me b Me' c (CN)6, wherein Me and Me' are each independently at least one of Ni, Cu, Fe, Mn, Co and Zn, 0<a≤2, 0<b<1, 0<c<1.
[0120] The positive electrode active material layer may further include a conductive agent to improve the conductivity of the positive electrode. The conductive agent may be selected from one or more of Super P, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphite, graphene, and carbon nanofibers.
[0121] The positive electrode active material layer may further include a binder to firmly bond the positive electrode active material and optional conductive agent to the positive electrode current collector. The binder may be at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyacrylic acid (PAA), polyvinyl alcohol (PVA), ethylene-vinyl acetate copolymer (EVA), styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), sodium alginate (SA), polymethacrylic acid (PMA), and carboxymethyl chitosan (CMCS).
[0122] The positive electrode current collector can be a conductive carbon sheet, metal foil, carbon-coated metal foil, porous metal plate, or a composite current collector. The conductive carbon material of the conductive carbon sheet can be selected from one or more of Super P, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphite, graphene, and carbon nanofibers. The metal material of the metal foil, carbon-coated metal foil, and porous metal plate can each be independently selected from at least one of copper, aluminum, nickel, and stainless steel. The composite current collector can be a composite of metal foil and a polymer-based film.
[0123] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0124] [Electrolytes]
[0125] The electrolyte conducts ions between the positive and negative electrodes. This application does not specify the type of electrolyte, and the electrolyte can be selected based on the needs. For example, the electrolyte can be liquid, gel, or solid.
[0126] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0127] In some embodiments, the electrolyte salt may be selected from at least one of sodium hexafluorophosphate, sodium bis(fluorosulfonyl)imide, sodium bis(trifluoromethanesulfonyl)imide, sodium trifluoromethanesulfonate, sodium tetrafluoroborate, sodium difluorophosphate, sodium perchlorate, and sodium chloride.
[0128] In some embodiments, the electrolyte contains an ester solvent, and the ester solvent contains at least one selected from ethylene carbonate, propylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, propylene carbonate, methyl acetate, ethyl propionate, and fluoroethylene carbonate.
[0129] In some embodiments, the electrolyte contains an ether solvent, and the ether solvent includes one or more of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, 1,3-dioxolane, tetrahydrofuran, methyltetrahydrofuran, diphenyl ether, and crown ether, and optionally includes one or more of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, and diethylene glycol dimethyl ether.
[0130] Electrolytes containing the aforementioned ether solvents are beneficial for reducing the overpotential of sodium ions and inducing uniform deposition of metal ions. Furthermore, the aforementioned solvents have strong anti-reduction properties, can promote the formation of a stable solid electrolyte interface on the surface of the guard metal, reduce side reactions during cycling, and improve the battery's coulombic efficiency and capacity retention after 100 cycles. Solvents containing one or more of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, and diethylene glycol dimethyl ether are beneficial for further improving the battery's coulombic efficiency and capacity retention after 100 cycles.
[0131] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, and additives that improve battery high or low temperature performance.
[0132] In some embodiments, the electrolyte further includes a sodium borate additive.
[0133] In some embodiments, the sodium borate additive comprises an ionic compound, the cation of the ionic compound comprises a sodium ion, and the anion of the ionic compound comprises a borate ion and a derivative thereof.
[0134] Sodium borate additives react with sodium metal to form boron-rich inorganic compounds, which in turn form an organic / inorganic composite protective layer with the interfacial protective layer, improving the battery's cycling performance. Furthermore, if the SEI membrane is damaged during battery cycling, sodium borate additives can continuously generate boron-rich inorganic compounds to repair the damage, further enhancing the battery's cycling performance.
[0135] In some embodiments, the sodium borate additive includes one or more of sodium difluorooxalatoborate and sodium bisoxalatoborate, and optionally includes sodium difluorooxalatoborate.
[0136] The electrolyte containing the sodium borate additive is beneficial for improving the coulombic efficiency of the battery and the capacity retention rate after 100 cycles. Among them, the electrolyte containing sodium difluorooxalatoborate further improves the coulombic efficiency of the battery and the capacity retention rate after 100 cycles.
[0137] In some embodiments, the mass content of the sodium borate additive is 0.01% to 1.8%, optionally 0.1% to 1.0%, based on the total mass of the electrolyte. In some embodiments, the mass content of the sodium borate additive is 0.01%, 0.02%, 0.04%, 0.06%, 0.08%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.2%, 1.4%, 1.6% or 1.8%, based on the total mass of the electrolyte.
[0138] Controlling the mass content of sodium borate additives to 0.01% to 1% is beneficial to improving the coulombic efficiency of the battery and the capacity retention rate after 100 cycles. Controlling the mass content of sodium borate additives to 0.1% to 0.5% can further improve the coulombic efficiency of the battery and the capacity retention rate after 100 cycles.
[0139] [Isolation film]
[0140] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical and mechanical stability can be selected.
[0141] In some embodiments, the material of the separator can be selected from at least one of polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester, and natural fibers. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0142] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be formed into an electrode assembly through a winding process or a lamination process.
[0143] In some embodiments, the secondary battery may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.
[0144] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. Alternatively, the outer packaging of the secondary battery can be a soft shell, such as a pouch-type soft shell. The soft shell can be made of plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0145] [Secondary battery]
[0146] A secondary battery includes an electrolyte and a negative electrode sheet, wherein the negative electrode sheet includes a current collector in some embodiments.
[0147] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape. For example, FIG2 shows a secondary battery 5 having a square structure as an example.
[0148] In some embodiments, the secondary battery further includes a positive electrode sheet and a separator.
[0149] In some embodiments, the secondary battery includes at least one of a lithium battery and a sodium battery.
[0150] In some embodiments, the secondary battery includes at least one of a potassium battery, a magnesium battery, and a zinc battery.
[0151] In some embodiments, the secondary battery is a negative electrode-less sodium battery.
[0152] Anode-free sodium batteries contain no negative electrode active material, only a negative electrode current collector. During initial charging, sodium ions at the cathode receive electrons, depositing sodium metal on the current collector surface to form a sodium metal phase. During discharge, the sodium metal converts to sodium ions and returns to the positive electrode, enabling cyclical charging and discharging. Compared to sodium-ion secondary batteries and sodium metal batteries, anode-free sodium batteries can achieve higher energy density because they are not limited by negative electrode materials.
[0153] In some embodiments, referring to FIG3 , the outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the separator can be formed into an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0154] [Battery Module]
[0155] In some embodiments, secondary batteries can be assembled into a battery module. The number of secondary batteries contained in the battery module can be one or more. The specific number can be selected by those skilled in the art according to the application and capacity of the battery module.
[0156] Figure 4 shows an example battery module 4. Referring to Figure 4 , within the battery module 4, multiple secondary batteries 5 may be arranged sequentially along the length of the battery module 4. Of course, any other arrangement is also possible. Furthermore, the multiple secondary batteries 5 may be secured together using fasteners.
[0157] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0158] [Battery Pack]
[0159] In some embodiments, the battery modules described above may be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art based on the application and capacity of the battery pack.
[0160] Figures 5 and 6 illustrate an example battery pack 1. Referring to Figures 5 and 6 , the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 can be positioned over the lower case 3 to form an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.
[0161] [Electrical devices]
[0162] In one embodiment of the present application, an electric device is provided, comprising at least one of a secondary battery according to any embodiment, a battery module according to any embodiment, or a battery pack according to any embodiment.
[0163] The electrical device includes at least one of the secondary batteries, battery modules, or battery packs provided in this application. The secondary batteries, battery modules, or battery packs can be used as power sources for the electrical device, or as energy storage units for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but is not limited thereto.
[0164] As an electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.
[0165] Figure 7 shows an example of an electric device. This device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery, a battery pack or battery module can be used.
[0166] Another example device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is generally required to be lightweight and thin, and may use a secondary battery as a power source.
[0167] Example
[0168] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.
[0169] 1. Preparation method
[0170] Example 1
[0171] 1) Preparation of current collector
[0172] Weigh 5 g of carboxymethyl cellulose (CMC) and add it to deionized water. Stir to fully dissolve the carboxymethyl cellulose. Then, apply the solution on the surface of the copper foil and transfer it to a vacuum drying oven for complete drying to prepare a current collector with an interface protection layer.
[0173] 2) Preparation of positive electrode sheet
[0174] 10wt% polyvinylidene fluoride binder is fully dissolved in N-methylpyrrolidone (NMP), 10wt% carbon black conductive agent and 80wt% positive electrode active material Na4Fe3(PO4)2P2O7(NFPP) are added, and stirred and mixed evenly to obtain positive electrode slurry; then the positive electrode slurry is evenly coated on the surface of the positive electrode collector copper foil, and after drying, cold pressing and slitting, the positive electrode sheet is obtained.
[0175] 3) Isolation film
[0176] Polypropylene film is used as the isolation film.
[0177] 4) Preparation of electrolyte
[0178] In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), sodium salt sodium hexafluorophosphate (NaPF6) was dissolved in ethylene glycol dimethyl ether (DME) organic solvent and stirred evenly, and then sodium difluorooxalatoborate (NaDFOB) additive was added, wherein the concentration of NaPF6 was 1 mol / L and the weight content of sodium difluorooxalatoborate was 0.25% based on the total mass of the electrolyte, i.e., the electrolyte of Example 1.
[0179] 5) Preparation of full battery
[0180] Preparation of a full anode-free battery: The positive electrode sheet, separator, and the aforementioned current collector are stacked in sequence, with the separator positioned between the positive and negative current collectors to provide insulation. The cells are then wound to form a bare cell. The tabs are welded to the bare cell, which is then encased in an aluminum casing and baked at 80°C to remove moisture. The electrolyte is then injected and sealed to produce an uncharged battery. The uncharged battery then undergoes a series of processes, including resting, hot and cold pressing, formation, shaping, and capacity testing, to produce a cathode-free sodium metal battery product.
[0181] Preparation of a full metal negative electrode battery: Place the above-mentioned current collector into a physical vapor deposition device, and pre-deposit a sodium metal phase on the current collector by ion sputtering to obtain a metal negative electrode plate. Stack the positive electrode plate, separator, and metal negative electrode plate in order, so that the separator is between the positive electrode plate and the metal negative electrode plate to act as an isolation. Then, wind the plate to obtain a bare cell, weld the tabs to the bare cell, and place the bare cell into an aluminum shell. Bake it at 80°C to remove water, then inject the electrolyte and seal it to obtain an uncharged battery. The uncharged battery then undergoes a series of processes, including standing, hot and cold pressing, formation, shaping, and capacity testing, to obtain a sodium metal battery product.
[0182] 6) Preparation of sodium electrolytic solution
[0183] Preparation of a sodium button battery without a negative electrode: stack the above-mentioned current collector, isolation membrane, sodium sheet, and sodium in order, so that the isolation membrane is placed between the negative electrode current collector and the sodium sheet to play an isolating role, then inject the electrolyte, seal, and assemble into a button battery.
[0184] Preparation of a metal anode-sodium button cell: Place the aforementioned current collector in a physical vapor deposition (PVD) apparatus and pre-deposit sodium metal onto the current collector via ion sputtering to form a metal anode electrode. The metal anode electrode, separator, sodium sheet, and sodium are stacked in sequence, with the separator positioned between the metal anode and sodium sheets to provide isolation. Electrolyte is then injected, the battery is sealed, and assembled into a button cell.
[0185] Examples 2 to 7
[0186] The batteries of Examples 2 to 7 were prepared in a similar manner to the battery of Example 1, except that the thickness of the interface protection layer was adjusted. The specific parameters are shown in Table 1.
[0187] The preparation method of the battery of Example 8 is similar to that of the battery of Example 1, but the preparation method of the current collector surface coating is adjusted. The preparation method is as follows:
[0188] Weigh 5g of carboxymethyl cellulose (CMC) and add it to deionized water. Stir to fully dissolve the carboxymethyl cellulose, then add 5g of single-walled carbon nanotubes and prepare a slurry after ultrasonic dispersion. The slurry is then coated on the surface of copper foil and then transferred to a vacuum drying oven for complete drying to prepare a current collector with an induced deposition layer.
[0189] Weigh 5g of CMC and add it to deionized water. Stir to fully dissolve the CMC. Then apply the solution on the surface of the induced deposition layer of the above-mentioned current collector with an induced deposition layer. Then transfer it to a vacuum drying oven and completely dry it to obtain a current collector with an interface protection layer and an induced deposition layer.
[0190] Examples 9 to 14
[0191] The batteries of Examples 9 to 14 were prepared in a similar manner to the battery of Example 8, except that the thickness of the interface protection layer was adjusted. The specific parameters are shown in Table 1.
[0192] Examples 15 to 20
[0193] The batteries of Examples 15 to 20 were prepared in a similar manner to the battery of Example 8, but the thickness of the induced deposition layer was adjusted. The specific parameters are shown in Table 1.
[0194] Examples 21 to 24
[0195] The preparation methods of the batteries of Examples 21 to 24 are similar to those of the battery of Example 8, but the components of the induced deposition layer are adjusted. The specific parameters are shown in Table 1.
[0196] Examples 25 to 31
[0197] The batteries of Examples 25 to 31 were prepared in a similar manner to that of Example 8, except that the content of the NaDFOB additive in the electrolyte was adjusted. The specific parameters are shown in Table 1.
[0198] Examples 32 to 35
[0199] The preparation methods of the batteries of Examples 32 to 35 are similar to those of the battery of Example 8, but the components of the interface protection layer are adjusted. The specific parameters are shown in Table 1.
[0200] Example 36
[0201] The preparation method of the battery of Example 36 is similar to that of the battery of Example 8, but the binder of the induced deposition layer is adjusted to polyvinylidene fluoride. The specific parameters are shown in Table 1.
[0202] Example 37
[0203] The preparation method of the battery of Example 37 is similar to that of the battery of Example 36, but the binder of the interface protection layer is adjusted to polyvinylidene fluoride. The specific parameters are shown in Table 1.
[0204] Example 38
[0205] The preparation method of the battery of Example 38 is similar to that of the battery of Example 8, but the type of additive in the electrolyte is adjusted. The specific parameters are shown in Table 1.
[0206] Examples 39 to 41
[0207] The batteries of Examples 39 to 41 were prepared in a similar manner to that of Example 8, except that the type of solvent in the electrolyte was adjusted. The specific parameters are shown in Table 1.
[0208] Example 42
[0209] The preparation method of the battery of Example 42 is similar to that of the battery of Example 1, but a metal phase is pre-deposited between the current collector and the interface protection layer. The specific parameters are shown in Table 1.
[0210] Comparative Example 1
[0211] The battery of Comparative Example 1 was prepared in a similar manner to that of Example 1, but no interface protection layer was provided on the surface of the current collector. Specific parameters are shown in Table 1.
[0212] Comparative Example 2
[0213] The preparation method of the battery of Comparative Example 2 is similar to that of the battery of Comparative Example 1, but no additive is added to the electrolyte. The specific parameters are shown in Table 1.
[0214] Comparative Example 3
[0215] The preparation method of the battery of Comparative Example 3 is similar to that of the battery of Comparative Example 2, but only an induced deposition layer is provided on the surface of the current collector. The specific parameters are shown in Table 1.
[0216] Comparative Example 4
[0217] The battery of Comparative Example 4 is prepared in a similar manner to the battery of Example 42, but no interface protection layer is provided on the surface. The specific parameters are shown in Table 1.
[0218] 2. Performance Testing
[0219] 1. Battery performance test
[0220] 1) Overpotential test
[0221] The overpotential test process is as follows: at 25 ° C, the prepared negative electrode current collector is placed on the button battery of the sodium sheet at 2 mA / cm 2 The constant current was discharged to 1 mAh, and the most negative potential obtained during the process was recorded as the overpotential. The test process of the comparative example and other embodiments was the same as above.
[0222] 2) First Coulombic efficiency test
[0223] The first coulomb test process is as follows: at 25 ° C, the prepared full battery is charged to 3.7V at a constant current of 1 / 3C, then charged at a constant voltage of 3.7V until the current drops to 0.05C to obtain the first charge capacity (Cc1), and then discharged to 2.5V at a constant current of 1 / 3C to obtain the first discharge capacity (Cd1). The battery coulomb efficiency is calculated according to the following formula:
[0224] Coulombic efficiency = initial discharge capacity (Cd1) / initial charge capacity (Cc1) × 100%. The test procedures for the comparative example and other embodiments are the same as above.
[0225] 3) Battery cycle capacity retention test
[0226] The battery capacity retention rate test process is as follows: at 25°C, the prepared full battery is charged to 3.7V at a constant current of 1C, then charged at a constant voltage of 3.7V until the current drops to 0.05C, and then discharged to 2.5V at 1C. The obtained capacity is recorded as the initial capacity (C0). Repeat the above steps for the same battery mentioned above, and record the discharge capacity (Cn) of the battery after the nth cycle at the same time. Then the battery capacity retention rate after each cycle is Pn=Cn / C0×100%. The 100 point values P1, P2...100 are used as the vertical coordinates, and the corresponding number of cycles is used as the horizontal coordinates to obtain a curve graph of the battery capacity retention rate and the number of cycles. During this test process, the first cycle corresponds to n=1, the second cycle corresponds to n=2,...the 100th cycle corresponds to n=100. The battery capacity retention rate data corresponding to the embodiment or comparative example in Table 2 are the data measured after 100 cycles under the above test conditions, that is, the value of P100. The test process of the comparative example and other embodiments is the same as above.
[0227] 3. Analysis of test results of various embodiments and comparative examples
[0228] Batteries of various examples and comparative examples were prepared according to the above methods, and various performance parameters were measured. The results are shown in Tables 1 and 2 below.
[0229] Table 1
[0230]
[0231]
[0232] Table 2
[0233]
[0234]
[0235] The above results show that the coatings in Examples 1-42 are formed on at least one side of the current collector and include an interface protective layer. A comparison of Examples 1-41 with Comparative Example 1, and Example 42 with Comparative Example 4, shows that the interface protective layer is formed on one side of the current collector copper foil. This interface protective layer reduces contact between the sodium metal and the electrolyte, helping to minimize side reactions between the two, effectively improving the battery's coulombic efficiency and capacity retention after 100 cycles.
[0236] From the comparison between Examples 8 to 14 and Examples 1 to 7, it can be seen that compared with the coating comprising only the carboxymethyl cellulose (CMC) interface protection layer, the coating further comprises a carbon nanotube induced deposition layer, and the carbon nanotube induced deposition layer is located between the current collector copper foil and the carboxymethyl cellulose (CMC) interface protection layer, which is more conducive to reducing the nucleation overpotential of sodium ions, further improving the coulombic efficiency of the battery and the capacity retention rate after 100 cycles, and the nucleation overpotential of sodium ions is reduced by more than 90% (reduction = (minimum nucleation overpotential in Examples 1 to 7 - minimum nucleation overpotential in Examples 8 to 14)). 14) / (the minimum nucleation overpotential in Examples 1 to 7) × 100%, the following algorithm is the same), the increase in coulombic efficiency and the capacity retention rate after 100 cycles is more than 20% (taking the increase algorithm of coulombic efficiency as an example, the increase = (minimum coulombic efficiency in Examples 8 to 14 - the maximum coulombic efficiency in Examples 1 to 7) / (minimum coulombic efficiency in Examples 1 to 7) × 100%, the increase algorithm of coulombic efficiency and the capacity retention rate after 100 cycles is the same), which greatly improves the cycle performance and safety of the battery.
[0237] From the comparison of Examples 1, 3 to 6 with Examples 2 and 7, and Examples 8, 10 to 13 with Examples 9 and 14, it can be seen that controlling the thickness of the carboxymethyl cellulose (CMC) interface protective layer to 15 nm to 1500 nm is beneficial to improving the coulombic efficiency of the battery and the capacity retention rate after 100 cycles or reducing the nucleation overpotential of sodium ions. From the comparison of Examples 1, 4 to 5 with Examples 3 and 6, and Examples 8, 11 to 12 with Examples 10 and 13, it can be seen that controlling the thickness of the carboxymethyl cellulose (CMC) interface protective layer to 50 nm to 500 nm is beneficial to further improving the coulombic efficiency of the battery and the capacity retention rate after 100 cycles or reducing the nucleation overpotential of sodium ions to a greater extent.
[0238] Comparison of Examples 8, 16-19 with Examples 15 and 20 shows that controlling the thickness of the carbon nanotube induced deposition layer to 50nm-2000nm can provide sufficient nucleation sites, which is beneficial for reducing the nucleation overpotential of sodium ions, improving the coulombic efficiency of the battery and the capacity retention rate after 100 cycles. The reduction in the nucleation overpotential of sodium ions exceeds 46%. Comparison of Examples 8, 17-18 with Examples 16 and 19 shows that controlling the thickness of the carbon nanotube induced deposition layer to 200nm-1000nm is beneficial for further reducing the nucleation overpotential of sodium ions and further improving the coulombic efficiency of the battery and the capacity retention rate after 100 cycles.
[0239] From the comparison of Examples 8, 21 to 24 with Comparative Example 1, it can be seen that the deposition-induced deposition layer contains carbon nanotubes, Super P, graphene, metallic silver or a Super P-carbon nanotube mixture, which can effectively reduce the nucleation overpotential of sodium ions and improve the coulombic efficiency of the battery and the capacity retention rate after 100 cycles. From the comparison of Examples 8, 21 to 22, 24 with Example 23, it can be seen that compared with the induced deposition layer containing only metal materials, the induced deposition layer containing carbon materials has a lower sodium ion nucleation overpotential, as well as a higher battery coulombic efficiency and capacity retention rate after 100 cycles. From the comparison of Examples 8, 24 with Example 22, it can be seen that compared with the graphene induced deposition layer, the carbon nanotube induced deposition layer or the Super P-carbon nanotube induced deposition layer can further reduce the nucleation overpotential of sodium ions and more significantly improve the coulombic efficiency of the battery and the capacity retention rate after 100 cycles.
[0240] From the comparison of Examples 8, 21 to 24 with Comparative Example 1, it can be seen that the deposition-induced deposition layer contains carbon nanotubes, Super P, graphene, metallic silver or a Super P-carbon nanotube mixture, and the electrolyte contains sodium difluorooxalatoborate (NaDFOB) additive, which is beneficial to further improve the coulombic efficiency of the battery and the capacity retention rate after 100 cycles.
[0241] From the comparison of Examples 8, 26 to 30 with Examples 25 and 31, it can be seen that, based on the total mass of the electrolyte, controlling the mass content of the sodium difluorooxalatoborate (NaDFOB) additive in the electrolyte to 0.01% to 1.8% is beneficial to improving the capacity retention rate of the battery after 100 cycles. From the comparison of Examples 8, 27 to 28 with Examples 26 and 30, it can be seen that, based on the total mass of the electrolyte, controlling the mass content of the sodium difluorooxalatoborate (NaDFOB) additive in the electrolyte to 0.1% to 1.0% can further improve the coulombic efficiency of the battery and the capacity retention rate after 100 cycles.
[0242] From the comparison of Examples 8, 32 to 35 with Comparative Example 3, it can be seen that the interface protective layer comprises carboxymethyl cellulose (CMC), polyacrylic acid (AA), polyvinylidene fluoride (PVDF), styrene-butadiene (SBR) or polyimide (PI), which is beneficial to improving the coulombic efficiency of the battery and the capacity retention rate after 100 cycles. The increase in the coulombic efficiency of the battery and the capacity retention rate after 100 cycles is more than 63%. From the comparison of Examples 8 and 33 with Examples 32, 34 to 35, it can be seen that compared with the interface protective layer comprising polyacrylic acid (AA), styrene-butadiene (SBR) or polyimide (PI), the interface protective layer comprising carboxymethyl cellulose (CMC) or polyvinylidene fluoride (PVDF) can significantly reduce the nucleation overpotential of sodium ions, further improving the coulombic efficiency of the battery and the capacity retention rate after 100 cycles.
[0243] From the comparison between Example 8 and Examples 32 to 35, and Example 37 and Example 36, it can be seen that the material of the control interface protection layer and the binder material in the induced deposition layer are at least partially the same, which is beneficial to reducing the nucleation overpotential of sodium ions and improving the coulombic efficiency of the battery and the capacity retention rate after 100 cycles.
[0244] From the comparison of Examples 8 and 38 with Example 25, it can be seen that the inclusion of sodium difluorooxalatoborate or sodium bisoxalatoborate in the electrolyte is beneficial to improving the coulombic efficiency of the battery and the capacity retention rate after 100 cycles. From the comparison of Example 8 and Example 38, it can be seen that the electrolyte containing sodium difluorooxalatoborate has better battery coulombic efficiency and capacity retention rate after 100 cycles than the electrolyte containing sodium bisoxalatoborate.
[0245] From the comparison of Examples 8, 39 to 41 with Comparative Example 3, it can be seen that the electrolyte containing ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether or tetrahydrofuran is beneficial to reducing the overpotential of sodium ions and improving the coulombic efficiency of the battery and the capacity retention rate after 100 cycles. From the comparison of Examples 8, 39 to 40 with Example 41, it can be seen that compared with the electrolyte containing tetrahydrofuran, the electrolyte containing ethylene glycol dimethyl ether, ethylene glycol diethyl ether or diethylene glycol dimethyl ether is beneficial to further improve the coulombic efficiency of the battery and the capacity retention rate after 100 cycles.
[0246] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any embodiments having substantially the same structure and effect as the technical concept within the scope of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the present application, any other embodiments that can be conceived by those skilled in the art and that combine some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A current collector having a coating, characterized in that: The coating layer at least includes an interface protection layer, and the coating layer is formed on at least one side of the current collector.
2. The current collector according to claim 1, characterized in that The coating layer further includes an induced deposition layer, and the induced deposition layer and the interface protection layer are sequentially arranged in a direction from close to the current collector to far away from the current collector.
3. The current collector according to claim 2, characterized in that The induced deposition layer is in direct contact with the surface of the current collector.
4. The current collector according to claim 2 or 3, characterized in that: The interface protection layer is in direct contact with the surface of the induced deposition layer.
5. The current collector according to any one of claims 1 to 4, characterized in that The interface protection layer comprises one or more of polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene copolymer, polyacrylic acid, and polyimide, and optionally comprises one or more of polyvinylidene fluoride and carboxymethyl cellulose.
6. The current collector according to any one of claims 1 to 5, characterized in that The thickness of the interface protection layer is 15 nm to 1500 nm, and can be optionally 50 nm to 500 nm.
7. The current collector according to any one of claims 2 to 6, characterized in that The induced deposition layer includes a conductive material, and the conductive material includes a carbon material and / or a metal material.
8. The current collector according to any one of claims 2 to 7, characterized in that The conductive material includes one or more of superconductive carbon black, carbon nanotubes, hard carbon, two-dimensional graphene, graphene quantum dots, gold, silver, copper, aluminum, iron, and nickel, and optionally includes one or more of Super P, carbon nanotubes, hard carbon, two-dimensional graphene, and graphene quantum dots.
9. The current collector according to any one of claims 2 to 8, characterized in that The thickness of the induced deposition layer is 50 nm to 2000 nm, and can be optionally 200 nm to 1000 nm.
10. The current collector according to any one of claims 2 to 9, characterized in that The induced deposition layer further comprises a binder, and the binder comprises one or more selected from polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene copolymer, polyacrylic acid, and sodium alginate.
11. The current collector according to any one of claims 2 to 10, characterized in that The binder material in the induced deposition layer is at least partially the same as the material of the interface protection layer.
12. The current collector according to any one of claims 1 to 11, characterized in that The current collector includes at least one of a metal foil, a metal foam current collector, a metal mesh current collector, a carbon felt current collector, a carbon cloth current collector, a carbon paper current collector and a composite current collector.
13. A secondary battery, characterized in that: The invention comprises an electrolyte and a negative electrode plate, wherein the negative electrode plate comprises the current collector according to any one of claims 1 to 12.
14. The secondary battery according to claim 13, wherein: The secondary battery includes at least one of a lithium battery and a sodium battery.
15. The secondary battery according to claim 13 or 14, characterized in that: The secondary battery is a negative electrode-free sodium battery.
16. The secondary battery according to any one of claims 13 to 15, characterized in that: The electrolyte contains an ether solvent, and the ether solvent includes one or more of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, 1,3-dioxolane, tetrahydrofuran, methyltetrahydrofuran, diphenyl ether, and crown ether, and optionally includes one or more of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, and diethylene glycol dimethyl ether.
17. The secondary battery according to any one of claims 13 to 16, characterized in that: The electrolyte also includes a sodium borate additive.
18. The secondary battery according to claim 17, wherein: The sodium borate additive includes one or more of sodium difluorooxalatoborate and sodium bisoxalatoborate, and optionally includes sodium difluorooxalatoborate.
19. The secondary battery according to claim 17 or 18, characterized in that: Based on the total mass of the electrolyte, the mass content of the sodium borate additive is 0.01% to 1.8%, and can be optionally 0.1% to 1.0%.
20. A battery module, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 13 to 19.
21. A battery pack, characterized in that: The secondary battery according to any one of claims 13 to 19 or the battery module according to claim 20 is included.
22. An electrical device, characterized in that: The battery comprises at least one selected from the group consisting of the secondary battery according to any one of claims 13 to 19, the battery module according to claim 20, and the battery pack according to claim 21.
Citation Information
Cited By
Negative-electrode-free secondary battery, modified graphite, modified current collector and preparation method thereof
CN119528135A
Negative electrode-free secondary battery, modified graphite, modified current collector and preparation method thereof
CN119528135B
Modified negative electrode current collector, preparation method and application thereof, and negative-electrode-free sodium metal battery
CN121964666A